2019
DOI: 10.1002/mop.32137
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of single and dual element bowtie microstrip antenna embedded with planar long wire for 5G wireless applications

Abstract: In this article, a low‐profile bowtie shaped planar antenna loaded with long wire is designed, analyzed, and fabricated, which is fed by microstrip line and presented with and without metallic reflector. It consists of a planar long‐wire antenna, which is designed at 27 GHz and terminated with the input impedance of a planar bowtie shaped element supported by defected ground structure. This terminating element works as a load resistance for long wire. Furthermore, two‐element antenna arrays with proposed bowti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In a similar study, this experiment was also done in novel size and not miniaturized. According to the results of the study, the compact rounded bowtie and the slotted bowtie antenna especially showed great potential for antennas to be used in air-coupled groundpenetrating radar (GPR) systems [17].…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…In a similar study, this experiment was also done in novel size and not miniaturized. According to the results of the study, the compact rounded bowtie and the slotted bowtie antenna especially showed great potential for antennas to be used in air-coupled groundpenetrating radar (GPR) systems [17].…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…The authors designed microstrip patches and a waveguide aperture antenna with embedded slots to obtain optimal performance, with an increased number of radiating elements at the 28 GHz frequency band [ 34 ]. Another bowtie-shaped antenna was designed on Rogers RT/Duroid 5880 substrate embedded with long wire supported by DGS to cover a relative BW of 27–29 GHz and with large dimensions [ 35 ]. CPW-fed wideband reflector corner bent antenna elements have been proposed for 5G terminals [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main structure consists of two FR4 dielectric layers and the top layer consists of three vertical dielectric parts, and therefore this method negatively affects the antenna compactness. In [ 7 ], single and double bowtie shaped MPAs with defected ground structures have been proposed for broadband wireless applications including 5G with 12 dBi stable gain. The single bowtie antenna operates in the 26.7–28.7 GHz frequency band, while the dual element bowtie antenna operates between 27.5 GHz and 28.3 GHz.…”
Section: Introductionmentioning
confidence: 99%